Pengaruh Disiplin Kerja Terhadap Efektivitas Pelayanan Publik di Kantor Kecamatan Pamona Timur - Indriyani Tandawuya, Novia; Mahardiana, Lina; Wirastuti, Wiri; Lamusa, Faruq (Universitas Muhammadiyah Pontianak, 2026)
Public service effectiveness requires adequate employee work discipline, particularly in ensuring timely and consistent service delivery. This study examines the effect of work discipline on public service effectiveness at the Pamona Timur District Office. A quantitative causal-associative approach was employed, involving 33 employees selected through census sampling. Data were collected using questionnaires and analyzed using simple linear regression. The results demonstrate that work discipline has a positive and significant effect on public service effectiveness (β = 0.508; p < 0.001; R² = 0.669). Strengthening employee work discipline is therefore essential for improving effective and reliable public service delivery.